2019
DOI: 10.1038/s41598-019-56667-6
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin hydrolase regulates the release of chemokines important for inflammation and wound healing by keratinocytes

Abstract: Bleomycin hydrolase (BLMH) is a well-conserved cysteine protease widely expressed in several mammalian tissues. In skin, which contains high levels of BLMH, this protease is involved in the degradation of citrullinated filaggrin monomers into free amino acids important for skin hydration. Interestingly, the expression and activity of BLMH is reduced in patients with atopic dermatitis (AD) and psoriasis, and BLMH knockout mice acquire tail dermatitis. Apart from its already known function, we have discovered a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…A recent report incriminated one of the catalytic enzymes from the NMF production cascade in regulation of the inflammatory response. Specifically, deficient expression of keratinocyte bleomycin hydrolase resulted, in addition to the decreased degradation of filaggrin monomers into free amino acids, in an increased release of pro-inflammatory chemokines that are upregulated in skin of AD patients compared to healthy individuals ( Riise et al ., 2019 ). Because FLG mutations remain the principal determinant of filaggrin expression and its downstream processing cascade, we quantified the levels of filaggrin breakdown products in the tape-stripped corneocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report incriminated one of the catalytic enzymes from the NMF production cascade in regulation of the inflammatory response. Specifically, deficient expression of keratinocyte bleomycin hydrolase resulted, in addition to the decreased degradation of filaggrin monomers into free amino acids, in an increased release of pro-inflammatory chemokines that are upregulated in skin of AD patients compared to healthy individuals ( Riise et al ., 2019 ). Because FLG mutations remain the principal determinant of filaggrin expression and its downstream processing cascade, we quantified the levels of filaggrin breakdown products in the tape-stripped corneocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Bleomycin hydrolase (BLMH) and SASPase activity are indispensable for processing profilaggrin and maintaining the texture and hydration of the stratum corneum, and decreased activity of BLMH or SASPase results in a marked decrease of filaggrin production in human skin. 117,118 Recently, it has also been observed that hyperactive JAK1 mutation induces "AD"like skin lesions while human JAK1 mutation may also be associated with AD skin lesion. 119 These mutant mice are essentially deficient in filaggrin and are therefore also used to explore the functional role of filaggrin in AD pathobiology.…”
Section: Engineered Mouse Mutantsmentioning
confidence: 99%
“…Several mouse models carrying inactivating mutations of SASPase (Sasp −/− ), 117 filaggrin (Flg ft/ft and Flg −/− ), 117 filaggrin–hornerin (FlgHrnr −/− ), 117 or bleomycin hydrolase (Blmh −/− ) 117 have been proposed as murine AD models. Bleomycin hydrolase (BLMH) and SASPase activity are indispensable for processing profilaggrin and maintaining the texture and hydration of the stratum corneum, and decreased activity of BLMH or SASPase results in a marked decrease of filaggrin production in human skin 117,118 . Recently, it has also been observed that hyperactive JAK1 mutation induces “AD”‐like skin lesions while human JAK1 mutation may also be associated with AD skin lesion 119 …”
Section: Currently Available “Ad” Animal Modelsmentioning
confidence: 99%
“…This enzyme, a neutral cysteine protease, reduces not only the DNA damaging activity of BLM in vitro but also in vivo [ 12 ]. The gene [ 36 ] has been identified in human lymphomas as well as in patients with atopic dermatitis and psoriasis [ 62 ] at different levels. In turn, the obvious assumption was that after addition of polyP to the BLM-treated cells an induction of the gene encoding for the BLM hydrolase will take place.…”
Section: Discussionmentioning
confidence: 99%
“…The amplified PCR products were obtained after 28–32 cycles (30 s at 94 °C, annealing for 45 s at 50 °C, primer extension for 30 s at 72 °C). For the amplification of the BLM hydrolase [ 60 , 61 , 62 ], the forward primer 5′-ACCAGCCCATTGACTTCC-3′ and the reverse primer 5′-TGTCCACCACCACTTCGT-3′ were used. The values were normalized with the expression levels of the reference housekeeping gene GAPDH (glyceraldehyde 3-phosphate dehydrogenase; NM_002046.3) with the primer pair Fwd, 5′-ACTTTGTGAAGCTCATTTCC-3′ and Rev, 5′-TTGCTGGGGCTGGTGGTCCA-3′.…”
Section: Methodsmentioning
confidence: 99%